A Study of the Impact of Bank Credit on the Performance of Micro, Small, and Medium Enterprises in the Province of Gorontalo - Juanna, Andi; Umar, Zainal Abidin; Kusuma, Citra Aditya (American Journal of Economics and Business Management, 2022)
In Indonesia, the vast majority of businesses belong to Micro, Small, and Medium Business (MSMEs). In 2014-2016, for example, the number of MSMEs was more than 57,900,000 units, and was estimated to grow to more than 59,000,000 units. Cooperatives and MSMEs Office of the Gorontalo Province (2018) states that this figure increased between 2012 and 2017. MSMEs had 42,523 units in 2012, but 81,776 units in 2016 or a 52% increase over 5 years. Out of this number, only 50 MSMEs are fostered by the government. Due to a lack of government budget, only a few MSMEs have been helped by the government. MSMEs received credit transactions from banks worth Rp 468,280,272,160, or a 250% increase from 2015. In this study, therefore, we analyze how much bank credits influences the development of MSMEs.Drawing on a descriptive research, this present study employed literature studies approach to conduct the process of searching, collecting, and analyzing data. The results revealed that the performance of the MSMEs sector in the first quarter of 2019 as a whole also improved. MSMEs lending in the first quarter of 2019 grew by 7.62% (yoy), an increase from the fourth quarter of 2018 which was 4.22% (yoy). This condition pushed the portion of MSMEs credit to total bank credit to increase to 27.93% from the previous 27.75%. The existence of MSMEs continues to be supported by Bank Indonesia through a policy on the percentage of credit that must be disbursed to MSMEs with a minimum portion of 20% of MSMEs loans. This portion in the first quarter of 2019 has been increased to 27% of total loans in the Province of Gorontalo.